Penerapan Solar Cell sebagai Sumber Energi Alternatif Dalam Meningkatkan Dissolved Oxygen Kolam Ikan Budidaya Papuyu (Anabas Testudineus) - Sari, Nurma; Nasrulloh, Amar Vijai; Fahrudin, Arfan Eko; Kastika, I Nyoman Eva; Amarina, Hasna; Nugraha, Adhitya Ade (Universitas Lambung Mangkurat, 2025)
Community service activities at Nana Fishery located in Guntung Paikat Village, Banjarbaru have been completed. The application of solar cell technology has been applied in the fisheries sector. Solar cell alternative energy technology has been applied in running water pumps to supply oxygen content in water. Water quality, especially in the fisheries sector, must always be maintained so that fish growth and development grow optimally. Partners have gained knowledge about solar cell technology which in this case has been directly applied in the fisheries sector. In this activity, two solar cell panels with a power of 100 watt- peak (WP) have been installed, the water pump used is 30-Watt DC, 5 DC lights with a power of 10 watts. The specifications of the two batteries have a power of 12 Volts, 50 Ah with a backup period of two days. In addition, an Arduino Uno-based timer is also installed which is programmed to be on for two hours and off for 30 minutes. Based on testing before being given a load, it has a voltage value of 13.8 Volts and after being given a load, the water pump and lights show a voltage value of 13.6 Volts.